Key differences between lakes and reservoirs modify climate signals: A case for a new conceptual model - Nicole M. Hayes; Bridget R. Deemer; Jessica R. Corman; N. Roxanna Razavi; Kristin E. Strock (Limnology and Oceanography Letters, 2017)
Abstract Lakes and reservoirs are recognized as important sentinels of climate change, integrating catchment and atmospheric climate change drivers. Climate change conceptual models generally consider lakes and reservoirs together despite the possibility that these systems respond differently to climate‐related drivers. Here, we synthesize differences between lake and reservoir characteristics that are likely important for predicting waterbody response to climate change. To better articulate these differences, we revised the energy mass flux framework, a conceptual model for the effects of climate change on lentic ecosystems, to explicitly consider the differential responses of lake versus reservoir ecosystems. The model predicts that catchment and management characteristics will be more important mediators of climate effects in reservoirs than in natural lakes. Given the increased reliance on reservoirs globally, we highlight current gaps in our understanding of these systems and suggest research directions to further characterize regional and continental differences among lakes and reservoirs.